A whole lot of holes. (2nd January 2022) - Harries, Judith
Abstract : The first book that comes to mind when thinking about 'books with holes' is the classic picture book by Eric Carle, starring a certain hungry caterpillar, but there are many more featured here, along with activities to inspire communication and language skills.